EAST ASIA, THE RESTORATION OF MEMORIES AND NARRATIVE OF RETURN - RYU, Suyun (International Journal of Korean Humanities and Social Sciences, 2019)
In the early 2000s, Hwang Seok-young published three full-length novels. They were The Old Garden (2000), The Guest (2001) and Sim-Cheong (2003). The return trilogy attracted much attention in that they were works that informed Hwang Seok-yeong’s return to the Korean literary world. He visited North Korea in 1989 and exiled in Germany until 1993. He was imprisoned shortly after returning home in 1993 and imprisoned until 1998. Conflict and anguish due to his personal history overlap in the three works. It was the thematic focus of ‘return’. ‘Return’ is not simply returning. Above all, it is an encounter with ‘self-absence’ and is the most positive return to think of ‘today’. Furthermore, the final goal is to reconcile with the present. Therefore, the three long-time narratives he published were Hwang Seok-young’s return process as a writer.